Machine learning based model for risk prediction after ST-Elevation myocardial infarction: Insights from the North India ST elevation myocardial infarction (NORIN-STEMI) registry. (1st September 2022) - Shetty, Manu Kumar; Kunal, Shekhar; Girish, M.P.; Qamar, Arman; Arora, Sameer; Hendrickson, Michael; Mohanan, Padhinhare P.; Gupta, Puneet; Ramakrishnan, S.; Yadav, Rakesh; Bansal, Ankit; Zachariah, Geevar; et al.
Abstract: Background: Risk prediction following ST-Elevation Myocardial Infarction (STEMI) in resource limited countries is critical to identify patients at an increased risk of mortality who might benefit from intensive management. Methods: North India ST-Elevation Myocardial Infarction (NORIN-STEMI) is an ongoing registry that has prospectively enrolled 3, 635 STEMI patients. Of these, 3191 patients with first STEMI were included. Patients were divided into two groups: development (n=2668) and validation (unseen) dataset (n=523). Various ML strategies were used to train and tune the model based on validation dataset results that included 31 clinical characteristics. These models were compared in sensitivity, specificity, F1-score, receiver operating characteristic area under the curve (AUC), and overall accuracy to predict mortality at 30 days. ML model decision making was analyzed using the Shapley Additive exPlanations (ShAP) summary plot. Results: At 30 days, the mortality was 7.7%. On the validation dataset, Extra Tree ML model had the best predictive ability with sensitivity: 85%, AUC: 79.7%, and Accuracy: 75%. ShAP interpretable summary plot determined delay in time to revascularization, baseline cardiogenic shock, left ventricular ejection fraction <30%, age, serum creatinine, heart failure on presentation, female sex, and moderate-severe mitral regurgitation to be major predictors of all-cause mortality at 30 days (P<0.001 for all). Conclusion: ML models lead to an improved mortality prediction following STEMI. ShAP summary plot for the interpretability of the AI model helps to understand the model's decision in identifying high-risk individuals who may benefit from intensified follow-up and close monitoring. Highlights: Risk stratification is an integral component of ST-Elevation Myocardial Infarction (STEMI) care. Limitations of logistic regression-based risk scores include statistical assumption of linear relationship between variables Scores not well validated in South-East Asian population with diverse ethnic group and different and risk factor profile. Machine Learning (ML) model overcomes all the limitations of the traditional logistic regression based models. ML model helps in identifying high-risk individuals requiring intensified treatment regime and a proper follow-up.